Evaluating an Ultrasonic Flaw Detector-Based Method to Characterize Solubility of Whey Protein Concentrate - M. Hauser; J. Amamcharla (Kansas Agricultural Experiment Station Research Reports, 2015)
One of the important characteristics of powders is their ability to quickly break down and disperse. Currently, the dairy foods industry does not have a reproducible method that can quantify this behavior. A previously developed method for an ultrasonic flaw detector was used to see if an ultrasound could characterize the dissolution of whey protein concentrate with a protein content of 80% (WPC80). For this study, an ultrasonic flaw detector equipped with a 1 MHz immersion transducer was operated in a pulse-echo mode. WPC80 was aged at 25°C and 40°C for 3 weeks. After powder addition, ultrasound, focus beam reflectance measurement (FBRM), and solubility index were taken at regular intervals for 30 minutes. The time of flight and amplitude of the first and second peak were collected so that the velocity and attenuation could be calculated. Graphs of velocity and attenuation over time showed that there were differences between powders stored at different temperatures. Powders stored at lower temperatures had higher ultrasound velocities at 1800 seconds. From the attenuation data, the peak height, peak time, and area under the attenuation were extracted. The FBRM and solubility index showed that powders stored at 25°C were more soluble and these powders had a higher relative velocity at 1800 s, smaller area under the attenuation curve, lower peak height, and higher peak time. Overall, an ultrasonic flaw detector can be used for examining dissolution behavior of WPC80.
Keywords: ultrasonic flaw detector; whey protein concentrate; solubility